Shaping Future Generation Through Innovative Methods of Teaching - Kaur, Manpreet (Indonesian Journal of Educational Science and Technology, 2024)
Innovation in education is the index of development and teacher is the facilitator in this globalize world. Teachers of today's world have to meet the needs of the present education system without compromising the ability of future generation. Educational technology has given birth to "Edudemic" and innovative methods of teaching which is the need of the day.  The present day teaching techniques need to be instrumental which are to be integrated with technologically advanced practices methods of teaching to meet the needs of the students. Innovations methods of teaching helps to prepare the requirement of the society is dynamic, enthusiastic, constructive and skillful students who can understand the community prognosis and work for the development of the society. Intuitive mind and Creativity is a divine gift and each individual has a certain amount of this gift. The purpose of this paper is to suggest useful innovative teaching methods that can be attempted in constructing knowledge to the students so that education leads to exploration, and innovation not to cramming.